Capacity Building: Fisherman’s Society Institution Empowerment Against the Industrial 4.0 Age in Indonesia - Lilik Ekowanti, R.; Ali Embi, Muhamad; Bakri Putra, Ahmad; Suraji; Nugroho, Arif (International Journal of Psychosocial Rehabilitation, 2019)
Local resource management strategy is a description of development management that tries to answer the challenges of development in the form of poverty, deteriorating environment, lack of community participation. Local resource management is a people centered development planning mechanism that emphasizes social learning technology and program formulation strategies that aim to improve community capacity through capacity building. A number of points in the management of local resources include: (1) Institutional strengthening that meets the needs of the fishing community at the local level and has an identity and recognized role (2) Management of local resources strengthens the ability to direct and address assets in the local fishing community to meet their needs (3) Strengthening institutions with the support of autonomous organizations and independent fishermen by utilizing modern technology. This study wants to try to provide a basis and analysis in strengthening the institutional (capacity building) of the Coastal Fishermen of Surabaya East Java in order to advance, independent and prosper.